Analisis Yuridis Penyelesaian Sengketa Kepemilikan Tanah Bersetifikat Ganda - Putri, Bela Muhdayani (Fakultas Syariah INSURI Ponorogo, 2023)
Land is becoming increasingly vulnerable due to disputes, one of which is the double certificate land dispute. Therefore, a wise attitude is needed to manage this land problem so that it is in line with what is mandated in the constitution. It is hoped that the birth of the UUPA will provide legal certainty for all people. Research problems: (1) What factors cause the issuance of multiple land certificates? (2) How are legal disputes resolved in cases of multiple land certificates? This research uses a normative juridical approach, the research specifications used are analytical descriptive and the data sources used are primary data and secondary data through literature and field studies. Analyze and process data using qualitative analysis.